Leve três, pague dois: uma análise das relações entre consumidores e camelôes - Tayt-son, Debora Bogéa da Costa (2013)
This study analyses the consumer relations involved in purchases from street vendors in Rio de Janeiro. Nine interviews were conducted with the goal of understanding these relations and try ing to identify behaviors that are similar or can be recognized as representative of one or more consumer facets presented by Gabr iel and Lang (2006). The data were collected f rom in - depth interviews and analyzed according to technical content analysis (BARDIN, 2011). The subjects, nine street vendor consumers , were interviewed from January to March, 2013, their ages range between 22 - 34 years old . The findings indicate that stre et vendor consumers are informed and are aware of the advantages and risks involved in this market. Furthermore, a strong presence of different emotions and feelings are noticed when purchasing from street vendors. It can be concluded that the street vendo r consumer can have different behaviors, sometimes simultaneously, that represent one or more facets from the nine presented by Gabriel and Lang (2006).